PHENETIC AND UNSUPERVISED MULTIVARIATE ANALYSIS SYZYGIUM POLYANTHUM (WIGHT) WALP - & et al., Abdulrahman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Myrtaceae family is widely distributed in Asia has been the largest group of plant; mainly trees and few shrubs. Distributed all over the world in tropical and subtropical areas. Syzygium is the largest genus with economical value found all over the Malaysian Peninsular. Evolutionary relationships within the Syzygium is unclear and there are currently no reliable criteria to divide the genus into manageable entities for systematic study. Species of Syzygium is the richest genus of woody plants in South East Asia with approximately 1000 or more species but little is known about the genus. Syzygium polyanthum Wight is one of the favourites Ulam that have been consumed for ages in Peninsular Malaysia and also as herbal medicine. The species is widely misunderstood due to extreme morphological variability, similarity in aroma and flavor. The species is substituted or adulterated with several other species. The study was aimed to construct phenetic tree and unsupervised multivariate analysis from morphological and anatomical the data matrix. Phenetic analysis, Principal component and hierarchical cluster analysis revealed they are two different cultivars species but inter variation exited among cultivars of same species. The above documented information has added new taxonomic information with regard to the identification of the cultivars in Peninsular Malaysia. The study recommends further study on de novo sequence of Serai kayu and Serai kayu hutan.